Experimentation of Basic Level BIPA Teaching Materials on Reading Proficiency at Islam Wittaya School - Ulfani, Ulfani; Febriyana, Mutia (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
This study aims to analyse the effectiveness of the BIPA teaching material